Association between dietary intakes of B vitamins and nonalcoholic fatty liver disease in postmenopausal women: a cross-sectional study - Li, Jiajie; Huang, Jingda; Lv, Yanqing; Ji, Huifan (Frontiers in Nutrition, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is increasingly common globally, particularly among postmenopausal women. Diet plays a fundamental role in the treatment of NAFLD. However, clinical research on the dietary intakes of B vitamins, specifically in postmenopausal women, is scant. Hence, it is imperative to study the impact of B vitamin dietary intake in postmenopausal women. Methods: This study utilized National Health and Nutrition Examination Survey (NHANES) data for 668 postmenopausal women. Logistic regression analysis was conducted to investigate the association of the intakes of B vitamins with hepatic steatosis and liver fibrosis prevalence. The analysis accounted for various covariates and employed restricted cubic spline analysis to examine potential nonlinear relationships. Additionally, interactions among age, diabetes, and B-vitamin intakes, as well as the interaction between folate and vitamin B12 intake, were explored. Results: Higher intakes of folate [0.30 (0.10-0.88)], choline [0.26 (0.07-0.95)], vitamin B1, and vitamin B2 were associated with a reduced risk of hepatic steatosis in postmenopausal women. The associations of niacin (P-nonlinear=0.0003), vitamin B1 (P-nonlinear=0.036), and vitamin B2 (P-nonlinear<0.0001) intakes with hepatic steatosis showed a nonlinear pattern. However, no significant associations were observed between the intakes of niacin, vitamin B6 and vitamin B12 and hepatic steatosis. Furthermore, there were no significant associations between B-vitamin intakes and liver fibrosis. No interaction effects were observed. Conclusion: Dietary intakes of folate, choline, vitamin B1, and vitamin B2 may be associated with liver steatosis in postmenopausal women, these results suggest that optimizing the intake of these specific B vitamins may have a protective effect against liver steatosis in postmenopausal women, offering valuable insights into potential dietary strategies to promote their well-being.